Magnetic nanoparticles influence the biological function of mesenchymal stem cells - Xinyue Li; Sheng Qin; Xiaoyun Liao; Yang Li; Aimei Liu (Scientific Reports)
Abstract Mesenchymal’ stem cells (MSC) are widely used for transplantation to treat various diseases due to their strong immune regulatory and tissue repair abilities. Magnetic nanoparticles (MNPs) can be used to track transplanted MSC. However, the potential impact of the MNPs we developed on MSC function remains unclear. In this study, we treated MSC with poly-L-lysine (PLL)-modified MNPs (MSC-MNPs) at a concentration of 0.1 µg/µL to assess their effects on MSC. The results showed that there were no significant effects on cell morphology, differentiation potential, proliferation, apoptosis, or the cell cycle after MSC were treated with MNPs. Interestingly, further experiments revealed that MNPs significantly enhanced the migratory capacity of MSC. Bio-Plex analysis revealed that MNPs promoted the expression of anti-inflammatory cytokines while inhibiting the secretion of pro-inflammatory factors. Flow cytometry also detected a significant increase in the number of MSC subpopulations, including CD184⁺MSC, CD106⁺MSC, and CD55⁺MSC, after MNPs labeling, which was further supported by proteomic analysis. Moreover, MSC-MNPs promoted the phenotypic transition of reactive astrocytes from A1 to A2 after coculture with activated astrocytes. In conclusion, MNPs have no cytotoxic effects on MSC labeling and significantly enhance their anti-inflammatory functions, offering new possibilities for the clinical application of MSC.